Modeling of Shear Strength in Rectangular Reinforced Concrete Beams - Hussein A. Azeez (Engineering and Technology Journal, 2009)
In this paper a model for the shear capacity of rectangular reinforced concrete beams is proposed. This modeling depends on statistical analysis for 101 experimental results from literatures, as will be indicated. These results are pure shear results and shear resistance is predicted by concrete only (without shear reinforcement). The ACI approach for predicting shear strength as the sum of diagonal cracking and 45◦ degree truss model predicts the shear strength of beams, with an average of experimental to predicted shear strength ratio of 1.4 with a coefficient of variation of 46.7%. In this study, experimental pure shear test results as much as possible are revised to study the shear behavior and then modeling it using statistical analysis, to reduce the ratio and coefficient of variation. This model gives average ratio of 1.003 and coefficient of variation of 20.90%. Also in this study, all the factors effecting shear capacity are introduced with separate modeling. These factors are, concrete compression strength (fc'), beam width (b), size of aggregate (da), shear span to depth ratio (a/d), and percentage of longitudinal reinforcement. Then assembly model for shear strength containing all these factors is presented and compared with experimental results.